Enhancing a Successful Pregnancy and Delivery After ICSI in Advanced-Age Woman with Concurrent Disorders: A Case Report - F Aghaz; Z Mokari; M Bakhtiari (JRI, 2020)
Background: The objective of this case presentation was describing a live birth in an advanced-age woman with an extremely enlarged uterus, an ovary with blocked fallopian tubes, hypothyroidism and generalized anxiety disorder caused by childbirth following intracytoplasmic sperm injection/embryo transfer (ICSI-ET) with autologous oocytes.  Case Presentation: A 47-year-old patient with an enlarged uterus due to recurrent multiple fibroids following myomectomy was referred to clinical laboratory with a high level of desire to follow the prescribed recommendations and approaches to retrieve her fertility. The patient underwent two cycles of oocyte retrieval and two rounds of frozen-thawed embryo transfer. To achieve a successful pregnancy after oocyte retrieval (birth weight of 3300 g at 38 weeks of gestation), a frozen/thawed embryo in the second cycle of ET was transferred. Conclusion: Usage of efficient planning and management of ICSI treatments in patient with autologous oocytes and concurrent disorders, can be used as a new approach to cure the affected individuals.